Mobile-Based Application to Integrate Vocational Learning and Career Learning in Mechatronics Engineering Vocational High School - Nurdianah, Evi; Sudira, Putu; Daryono, Rihab Wit (Universitas Pendidikan Ganesha, 2022)
A new learning paradigm is needed by Vocational High Schools (SMK) to adapt vocational learning to the needs of the world of work in the era of industrial revolution 4.0. Changes in the structure of employment patterns due to the loss of existing jobs and the emergence of new job opportunities required the need to strengthen vocational schools as education for occupation and also as education for career development. Especially in mechatronics engineering vocational high school, which was closely related to industrial technology 4.0. This study aims to produce a mobile-based application to support the integration of vocational learning and career learning activities in mechatronic engineering vocational high schools. Product development used the research and development methods with the development stages was adapting the Holistic 4D model, namely the Define, Design, and Develop stages. Data was collected using observation sheets and questionnaires that had been validated by experts. The data analysis method used is quantitative data analysis. The results of expert reviews and operational trials showed that the learning media application developed was in the very feasible category with an average assessment score of 3.55. This result showed that the mobile-based application developed was feasible and can be used for the career development of vocational students with mechatronic engineering competence. Mobile-based application developed can be used to facilitate learner-centred projects, such as self-directed learning, collaborative learning, and project management.